Integrated Analytical Study for the Somes Metalic Artefact Discoveri in Ibida Site, Romania - Viorica VASILACHE; Dan APARASCHIVEI; Ion SANDU; Violeta VASILACHE; Ioan Gabriel SANDU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2012)
The paper presents the results of the analyses conducted using the SEM-EDX and micro-FTIR co-assisted techniques, on several metallic artefacts unearthed during the excavations at the (L)Ibida archaeological site in Slava Rusă, Tulcea County, Romania, that took place between 2001 and 2008. The data produced is of use in identifying several archaeometrical structural and compositional features which allow for the identification of the origin of the ores, of the alloy type, and of the manufacturing technology. A series of new data is thus produced, that can consolidate the three databases of scientific conservation of metallic artefacts (iarchaeometallurgy/archaeometry/historiography, ii-museum exhibiting, iii-tinerate/transfer/exchange/trade).